Location-based management system now and in the future - Seppänen, Olli (Lean Construction, 2020)
In location-based planning, locations are used as the basic unit of planning and control. The goal is to have trades flow through locations continuously, without breaks. The benefits of continuous work include increased learning effects, increased productivity, clear directions to crew members and a smaller risk of subcontractor crews leaving the project or charging for waiting time. Multiple approaches fall under the category of location-based planning and control and this chapter focuses on two more recent approaches: the Location-based Management System (LBMS) and takt planning and control. The approaches are compared and contrasted throughout the chapter. Regarding planning before production starts, the key elements of location-based planning are reviewed. The Location Breakdown Structure is a critical early decision where the project is divided into physical locations. Tasks include similar scope by the same crew in multiple locations and durations are based on quantities and resources. The plan is visualised in a flowline diagram where flow through the locations can be seen across multiple locations. LBMS expands on the well-known Critical Path Method (CPM) algorithm and adds location-based elements on top of it. For instance, logic can be automated if it repeats in multiple locations. Additionally, the LBMS algorithm makes it possible to calculate a start date which enables continuous work, and the default planning assumption is that all tasks are performed continuously. Schedule optimisation attempts to minimise the project duration by aligning production rates so that all crews flow through the project at the same rate. During production, the actual production rates and labour consumptions are tracked by recording completed quantities in locations. These rates are used to calculate forecasts of future problems if control actions are not implemented. LBMS control is based on preventing these production problems by reacting immediately to any alarms calculated in the LBMS schedule. There are many empirical studies about LBMS control which demonstrate that it is possible to proactively control production rates and prevent production problems by focusing on alarms. Productivity can be improved and durations shortened compared to traditional CPM. However, takt planning and control has a slightly different process than LBMS and although empirical evidence is still scant, there is a lot of anecdotal evidence that takt planning and control may result in even larger improvements. More evidence is needed in future research and potentially the systems could be combined in various combinations depending on project characteristics. This chapter begins with a very short history of location-based planning, and presents location-based planning system and location-based controlling system. Although the differences between Critical Path Method and Location-based Management System (LBMS) algorithms, most of the emphasis is on discussing the production system risk and how to plan optimal schedules using LBMS or takt planning methods. A location-based management system starts from the assumption that the best way to plan and monitor progress of work in a construction project is based on physical locations. The chapter deals with a discussion of open research questions and potential future research directions. It argues that other methods, such as cost-loading schedules, management of detailed design, scheduling of deliveries, and safety aspects, are also heavily dependent on location. The Location Breakdown Structure is one of the most important up-front planning decisions in LBMS.